Survey of Notified Bodies reveals very limited use of conditional certification for high-risk medical devices - Dobrzynska, A.; Rejon-Parrilla, J. C.; Epstein, D.; Aranda-López, J.; Fraser, A. G.; Blasco-Amaro, J. A. (Frontiers in Medical Technology, 2025)
The aim was to identify the experiences of Notified Bodies (NBs) in Europe in applying restrictions or limitations to certificates for high-risk medical devices. A survey examining NB practices regarding restrictions or limitations applied to Class III and IIb implantable medical devices was conducted as part of the CORE-MD Horizon 2020 project. Thirteen NBs responded; three had issued certificates of conformity with restrictions or limitations. NBs reported challenges in collecting and providing data on conditional certification, which would likely increase their workload. Enhancing clarity of regulatory standards, improving data transparency, fostering stakeholders' collaboration, and providing targeted training are essential to ensure uniform and homogeneous application of conditional certifications across the EU.